A focus group interview with health professionals: establishing efficient transition care plan for older adult patients in Korea - Chan Mi Park; Seung Jun Han; Jae Hyun Lee; Jin Lim; Sung do Moon; Hongran Moon; Seo-Young Lee; Hyeanji Kim; Il-Young Jang; Hee-Won Jung (BMC, 2022)
Abstract Background Although transition care planning can affect the functional status and quality of life after acute hospitalization in older adults, little is known on problems associated with discharge planning in acute care hospitals in Korea. We aimed to investigate barriers and possible solutions on transfer planning of complex older patients in this study. Methods We used focus group interviews with the application of framework analysis. Twelve physicians providing inpatient care from 6 different institutions in Korea participated in the interview. Facilitating questions were extracted from 2 roundtable meetings prior to the primary interview. From transcribed verbatim, themes were constructed from corresponding remarks by participants. Results We revealed two main domains of the barrier, which included multiple subdomains for each of them. The first domain was a patient factor barrier, a composite of misperception of medical providers' intentions, incomprehension of the healthcare system, and communication failure between the caregivers or decision-makers. The second domain, institutional factors included different fee structures across the different levels of care, high barrier to accessing health service in tertiary hospitals or to be referred to, the hardship of communication between institutions, and insufficient subacute rehabilitation service across the country. Conclusions Through the interview, physicians in the field recognized barriers to a smooth transition care process from tertiary level hospitals to community care, especially for older adults. Participants emphasized both the patients and hospital sides of adjustment on behaviors, communication, and greater attention for the individuals during the transition period.